Circadian Light Source Based on KxNa1-xLuS2:Eu2+ Phosphor. (27th October 2017) - Jarý, Vítězslav; Havlák, Lubomír; Bárta, Jan; Rejman, Martin; Bystřický, Aleš; Dujardin, Christophe; Ledoux, Gilles; Nikl, Martin
Abstract : The presented work describes a functional demonstration device representing the source of white light with tunable color correlated temperature. Tunability is achieved by using two different kinds of excitation diodes (nearUV and blue) in combination with a proper Kx Na1-x LuS2 :Eu 2+ phosphor. Its luminescence due to the Eu 2+ 5 d –4 f allowed transition covers a broad emission region in visible range under both nearUV and blue excitations. The possibility to change the intensity ratio of the excitation diodes yields the changes of the output color correlated temperature. These changes are clearly demonstrated by shifts in the CIE color space; light quality is also quantified and discussed using CRI (color rendering index) and CQS (color quality scale) metrics.